Reference architecture of the telecom network security protection system for cloud network convergence - Jian ZHANG; Hongyu TANG; Wentao LIU; Mingxia BO (Dianxin kexue)
Cloud network convergence has become a development trend in the field of cloud computing and a key step in the strategic transformation of telecom operators.Firstly,the development status of cloud network convergencewas expounded from the aspects of its connotation,typical application scenarios and the reconstruction of telecom network by cloud network convergence.Then,the security requirements of telecom network for cloud network convergencewere analyzed from three aspects.Based on the analysis of security requirements,the overall security protection architecture of telecom network for cloud network convergence was put forward,including the construction of basic security protection system and the software-defined security protection system,and the specific levels and contents of the basic security protection system and the software-defined security protection system were elaborated.Finally,the prospect of the future was prospected.